A combination of flexible and rigid bronchoscopy in the successful removal of a residual fish bone from a peripheral bronchus: A case report - Shao, Hanqing; Li, Shuxian; He, Jing; Wu, Lei; Chen, Zhimin (Frontiers in Pediatrics, 2023)
Although rigid bronchoscopy remains the gold standard for the management of foreign body (FB) inhalation, sometimes it still misses residual FBs. Inhalation of sharp FBs by infants is an uncommon but hazardous occurrence, which presents a significant challenge and demands expertise in therapeutic bronchoscopy. Particularly, residual sharp FBs in the peripheral tracheobronchial tree may pose challenging management problems for bronchoscopists. Herein, we describe the case of 1-year-old girl, who presented with persistent atelectasis in the left lower lobe for 20 days without responding to antibiotic therapy after removal of fish bone by rigid bronchoscopy at local hospital. Flexible bronchoscopy at our department showed a residual fish bone in the outer basal segment of the left lower lobe. A combined flexible and rigid bronchoscopy was then applied, and a fish bone measuring 1.5 cm in length was extracted on multiple attempts without any complications. Thus, our reports demonstrated that removal of challenging residual sharp FBs in the distal airways is possible with the aid of combined flexible and rigid bronchoscopy by an experienced multidisciplinary team. Additionally, a physician should pay special attention to abnormal chest images after removal of FBs.